Elevated Temperatures Shorten the Spawning Period of Silver Carp (Hypophthalmichthys molitrix) in a Large Subtropical River in China - Xia, Yuguo; Li, Xinhui; Yang, Jiping; Zhu, Shuli; Wu, Zhi; Li, Jie; Li, Yuefei (Frontiers in Marine Science, 2021)
Global warming is influencing the life history traits of fishes globally. However, the impacts of elevated temperature on fish reproduction are diverse in different regions. Previous studies have revealed that the spawning timing of silver carp (Hypophthalmichthys molitrix) in the Pearl River, in China, has changed over the past decade. However, few studies have explored the potential reasons, which are critical for determining fishing-moratorium periods and developing sustainable fisheries. The current study used discharge suitability index (DSI), temperature suitability index (TSI), correlation and time-series analyses to determine (i) the optimal discharge and temperature for silver carp spawning; (ii) relationships among the thermal regime, hydrological parameters, and spawning timing based on an 11-year time-series dataset. Our results indicated that the most suitable discharge and temperature for silver carp spawning were 13,000–15,000 m3/s and 25–26°C, respectively. The start date of spawning fluctuated with a slight tendency to delay, while the spawning peak and end date obviously occurred earlier during the study period. Correlation analyses suggested that the increasing average temperature between January and March likely caused the initial spawning delay. Moreover, elevated temperatures in August and September probably promoted the anticipated end of silver carp spawning. However, increases in discharge did not significantly correlate with the start of spawning but were significantly and positively correlated with the spawning peak. These results indicated that elevated temperatures shorten the spawning period of silver carp in the Pearl River. Moreover, the initial spawning of silver carp seems to be triggered by temperature rather than changes in discharge; flow pulses can probably create more suitable spawning niches for H. molitrix. This study enhances our understanding of the effect of warming on fish reproduction in subtropical regions.